Single and Mixed Feedstocks Biorefining: Comparison of Primary Metabolites Recovery and Lignin Recombination During an Alkaline Process - Berchem, Thomas; Schmetz, Quentin; Lepage, Thibaut; Richel, Aurore (Frontiers in Chemistry, 2020)
Cannabis sp. and Euphorbia sp. are potential candidates as indoor culture for the extraction of their high value-added metabolites for pharmaceutical applications. Both residual lignocellulosic materials recovered after extraction are studied in the present article as single or mixed feedstocks for a closed-loop bioprocesses cascade. An alkaline process (NaOH 3%, 30min 160°C) is performed to separate the studied biomasses into their main components: lignin and cellulose. Results highlight the advantages of the multi-feedstocks approach over the single biomass in term of lignin yield and purity. Since the structural characteristics of lignin affect the potential applications, a particular attention is drawn on the comprehension of lignin structure alteration and the possible interaction between them during single or mixed feedstocks treatment. FTIR and 2D-NMR spectra revealed similar profiles in term of chemical functions and structure rather than novel chemical bonds formation inexistent in the original biomasses. In addition, thermal properties and molecular mass distribution are conserved whether hemp or euphorbia are single treated or in combination. A second treatment was applied to investigate the effect of prolonged treatment on extracted lignins and the possible interactions. Aggregation, resulting in higher molecular mass, is observed whatever the feedstocks combination. However, mixing biomass does not affect chemical structures of the end product. Therefore, our paper suggests the possibility of gathering lignocellulosic residues during alkali process for lignin extraction and valorization, allowing to forecast lignin structure and make assumptions regarding potential valorization pathway.